Economic development in Africa report 2014: catalysin investment for transformative growth in Africa - United Nations Conference on Trade and Development (UNCTAD) (2014)
Africa has experienced high and continuous economic growth in the past decade, prompting analysts to argue that the continent has reached a turning point in its development history and is poised to play a more significant role in the global economy in the twenty-first century.